2021
DOI: 10.3889/oamjms.2021.6424
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Purple Passion Fruit Extract Cream (Passiflora edulis Sims var. Edulis) 6% against Striae Distensae

Abstract: ABSTRACT Background: Striae distensae is a skin disorder that causes cosmetic and psychological problems. Purple passion fruit (Passiflora edulis Sims var. Edulis) is widely cultivated, especially in North Sumatra. The seeds are abundant and unused industrial waste. Purple passion fruit seeds contain piceatannol, ascorbic acid, flavonoids, resveratrol, hydroalcohols and sterols which play a role in the repair of striae distensae through anti-inflammatory mechanisms, increase fibroblast proliferation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…P. edulis seed extract exhibits antibacterial activity against Propionibacterium acnes [78], and this antibacterial activity of the extract may have contributed to the improvement of acne vulgaris in the human studies. In addition, another human study demonstrated that application of a cream containing 6% P. edulis seed extract improved the symptoms of striae distensae, a common form of skin scarring [79]. Evidently, P. edulis seed extract can contribute to the improvement of skin disorders such as acne vulgaris and striae distensae when applied to the skin.…”
Section: Effect On Skinmentioning
confidence: 98%
“…P. edulis seed extract exhibits antibacterial activity against Propionibacterium acnes [78], and this antibacterial activity of the extract may have contributed to the improvement of acne vulgaris in the human studies. In addition, another human study demonstrated that application of a cream containing 6% P. edulis seed extract improved the symptoms of striae distensae, a common form of skin scarring [79]. Evidently, P. edulis seed extract can contribute to the improvement of skin disorders such as acne vulgaris and striae distensae when applied to the skin.…”
Section: Effect On Skinmentioning
confidence: 98%
“…Although no side effects have been reported from the topical use of its cream, limited scientific evidence is available regarding its use and safety among pregnant women Aryunisari et al (2021).…”
Section: Humanmentioning
confidence: 99%
“…Striae distensae mostly occurs in puberty (6% -86%) and obesity (43%). [1][2][3][4][5][6][7] Striae distensae can arise from several causes, including rapid changes in body weight, adolescent growth, use of corticosteroids, Cushing's syndrome, and commonly appearing on the buttocks, thighs, knees, lumbosacral region, breasts and upper arms in men. The mechanism associated with the formation of SD is not completely understood, but this disorder is the result of connective tissue discontinuity, which leads to atrophy of the dermis.…”
Section: Introductionmentioning
confidence: 99%